Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Air Minum Isi Ulang Rava Water Di Kecamatan Percut Sei Tuan - Evi Syuriani Harahap (Islamic Education Journal, 2023)
This study aims to determine the effect of customer service quality on customer satisfaction. This research is a type of descriptive research. The population of this research is the people who live in Dusun X Tembung Village, Percut Sei Tuan District. While taking samples in this study using Random Sampling Techniques (Random). The data analysis technique used in this study is the Validity Test, Reliability Test, Normality Test and One Sample T-Test. The calculation results show that from the test table for one of the samples above, it can be seen that the t-count value is 27.324. The value of df (degrees of freedom) is 0.000. Thus the alternative hypothesis (H1) which reads that consumer satisfaction is satisfied with the service quality of Rava Water Refill Drinking Water. is "accepted".